KAJIAN EROSI DAN POTENSI SEDIMENTASI DI DAS KAHAYAN PROVINSI KALIMANTAN TENGAH - Raden Haryo Saputra (Lambung Mangkurat University Press, 2019)
Management of swampy areas is inseparable from the management of watersheds. Erosion and sedimentation in the watershed affect the quality and quantity of river water entering the swamp area. One indicator of erosion is visible from the murky waters of the Kahayan River, while it is not yet known how much erosion and sedimentation potential occurs in the Kahayan watershed so that the study is needed for integrated Kahayan watershed management. This study aims to investigate the amount of erosion, analyze the level of erosion danger (TBE), and the magnitude of the results of sediments that occur in the Kahayan watershed. Analysis of land area and land units based on Geographic Information Systems. Estimates of estimated erosion rates use the Universal Soil Loss Equation (USLE) method, and sediment yields use the Soil Conservation Service-United States Department of Agriculture (SCS-USDA) method by considering the weighting of land units to their total area. The estimated amount of erosion that occurred in the Kahayan watershed is 13.19 tons / ha / year with TBE consisting of very mild categories 47.65%, mild 50.99%; moderate 0.25%; weight 1.12% and very heavy 0%. Specifically for areas with heavy category TBE, the total score of the three physical character factors of the watershed (slope, soil type according to its sensitivity to erosion, and rainfall intensity) was obtained by 184 with the direction of land use being a protected area. Based on the value of Sediment Delivery Ratio (SDR), the sediment yield in the Kahayan watershed is 169,115 tons / year and according to the Regulation of the Director-General of Land Rehabilitation and Social Forestry, the sediment yields in the Kahayan watershed are included in the good category.